ANALISIS PERMASALAHAN PENGANGGURAN DI INDONESIA - Suci Frisnoiry; Harry M. W. Sihotang; Nazwah Indri; Tiolina Munthe (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This study aims to identify the factors that influence the unemployment rate and its impact on the economic and social welfare of the community. The research method uses a literature study. The findings show that factors such as inequality in labor supply and demand, government policies that are less pro-people, and population growth are the main causes of high unemployment. Although the government has taken measures, such as the allocation of funds for handling COVID-19 and incentive programs, the decline in unemployment has not been significant. Recommendations include policies that support increased employment, investment in education and skills training, gender inclusion in the workforce, and cooperation between the government, private sector and civil society to create sustainable employment. With these measures, Indonesia is expected to reduce its unemployment rate and create a more stable and inclusive economy.